Crossed lines [large type] - Delamere, Jennifer (Delamere, Jennifer. Love along the wires, 2021)
"Mitchell Harris is captivated by Emma Sutton, but when his best friend also falls in love with her and asks for help writing her letters, he's torn between desire and loyalty. Longing for a family, Emma is elated when she receives a love note from a handsome engineer but must decide between the writer of the letters and her growing affection for Mitchell"--